(untitled) (International Seven Journal of Multidisciplinary, 2025)
Objective: To report the case of a patient with Bipolar Affective Disorder (BAD) who was admitted to a psychiatric referral hospital. Methods: A descriptive, restrictive, and longitudinal study was analyzed in clinical data in the brief hospitalization sector of the mental health reference hospital in May 2024. Data collection was based on medical records and the consent form of the patient and her companion. Results Case Report: The patient presented psychotic break, auditory delusions and aggressive behavior during hospitalization. Treatment included antipsychotics, nutritional adjustments and metabolic monitoring, laboratory tests that showed changes in glucose, and inflammatory indicators. Family support and multidisciplinary follow-up were essential for the patient’s recovery. Final considerations: The study highlights the management of BAD, the importance of an integrated approach including psychiatric, nutritional and family support.